Impact of Roommates on MDRO Spread in Nursing Homes. (October 2020) - Gussin, Gabrielle M.; Kleinman, Ken; Singh, Raveena D.; Saavedra, Raheeb; Heim, Lauren; Estevez, Marlene; Catuna, Tabitha D.; Lee, Eunjung; Osalvo, Avy; Evans, Kaye D.; Shimabukuro, Julie A.; McKinnell, James A.; et al.
Abstract : Background: Addressing the high burden of multidrug-resistant organisms (MDROs) in nursing homes is a public health priority. High interfacility transmission may be attributed to inadequate infection prevention practices, shared living spaces, and frequent care needs. We assessed the contribution of roommates to the likelihood of MDRO carriage in nursing homes. Methods: We performed a secondary analysis of the SHIELD OC (Shared Healthcare Intervention to Eliminate Life-threatening Dissemination of MDROs in Orange County, CA) Project, a CDC-funded regional decolonization intervention to reduce MDROs among 38 regional facilities (18 nursing homes, 3 long-term acute-care hospitals, and 17 hospitals). Decolonization in participating nursing homes involved routine chlorhexidine bathing plus nasal iodophor (Monday through Friday, twice daily every other week) from April 2017 through July 2019. MDRO point-prevalence assessments involving all residents at 16 nursing homes conducted at the end of the intervention period were used to determine whether having a roommate was associated with MDRO carriage. Nares, bilateral axilla/groin, and perirectal swabs were processed for methicillin-resistant Staphylococcus aureus (MRSA), vancomycin-resistant enterococcus (VRE), extended-spectrum β-lactamase (ESBL)–producing Enterobacteriaceae, and carbapenem-resistant Enterobacteriaceae (CRE). Generalized linear mixed models assessed the impact of maximum room occupancy on MDRO prevalence when clustering by room and hallway, and adjusting for the following factors: nursing home facility, age, gender, length-of-stay at time of swabbing, bedbound status, known MDRO history, and presence of urinary or gastrointestinal devices. CRE models were not run due to low counts. Results: During the intervention phase, 1, 451 residents were sampled across 16 nursing homes. Overall MDRO prevalence was 49%. In multivariable models, we detected a significant increasing association of maximum room occupants and MDRO carriage for MRSA but not other MDROs. For MRSA, the adjusted odds ratios for quadruple-, triple-, and double-occupancy rooms were 3.5, 3.6, and 2.8, respectively, compared to residents in single rooms ( P = .013). For VRE, these adjusted odds ratios were 0.3, 0.3, and 0.4, respectively, compared to residents in single rooms ( P = NS). For ESBL, the adjusted odds ratios were 0.9, 1.1, and 1.5, respectively, compared to residents in single rooms ( P = nonsignificant). Conclusions: Nursing home residents in shared rooms were more likely to harbor MRSA, suggesting MRSA transmission between roommates. Although decolonization was previously shown to reduce MDRO prevalence by 22% in SHIELD nursing homes, this strategy did not appear to prevent all MRSA transmission between roommates. Additional efforts involving high adherence hand hygiene, environmental cleaning, and judicious use of contact precautions are likely needed to reduce transmission between roommates in nursing homes. Funding: None Disclosures: Gabrielle M. Gussin, Stryker (Sage Products): Conducting studies in which contributed antiseptic product is provided to participating hospitals and nursing homes. Clorox: Conducting studies in which contributed antiseptic product is provided to participating hospitals and nursing homes. Medline: Conducting studies in which contributed antiseptic product is provided to participating hospitals and nursing homes. Xttrium: Conducting studies in which contributed antiseptic product is provided to participating hospitals and nursing homes.